Determinants and Geopolitical Capabilities of the State of Switzerland: A study in Geopolitical - Atheeb, Qasim (Al-Adab Journal, 2023)
Switzerland is one of the most powerful countries politically and economically. It possesses an important geopolitical in the international balance of power, despite its lack of strength. Therefore, the research deals with the study of the natural and human geopolitical determinants and the natural, economic and political geopolitical capabilities. It is an attempt to identify the nature of the strengths in Switzerland despite the great challenges. The research concludes that the State of Switzerland is able to transform the geopolitical determinants into sources of power, based on the nature of its political system, its adoption of the principle of neutrality and the nature of its society seeking peace and action.